Energy Recovery from Split-Type Air Conditioners: Experimental Analysis of Integrated Water Heating Systems with Different Refrigerants - Haolia Rahman; Paulus Sukusno; Ainun Nidhar (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2025)
Air conditioning (AC) systems use the evaporator to absorb heat from the indoor air to provide cooling. By utilizing the condenser side, these systems can also operate as heat pumps for water heating. However, such applications remain limited in Indonesia. This study experimentally investigates a modified split-type AC unit retrofitted with a 40 L insulated hot-water tank and a 10 m long, 5/8" diameter spiral copper tube condenser. Experiments were conducted over 180 minutes using R-22 and hydrocarbon (HC-290) refrigerants, with parameters recorded at 10-minute intervals. Results indicate that the modified system can simultaneously provide cooling and water heating with significant energy recovery. Using R-22, the system achieved electricity savings of 5.014 kWh/day (53.3%) with a payback period of 10.0 months. The HC refrigerant yielded savings of 4.384 kWh/day (47.8%) with an 11.4-month payback period. The measured cooling and heating coefficients of performance (COP) were 3.89 and 4.89, respectively. Unlike prior studies focused on theoretical aspects, this work provides experimental validation under realistic household conditions and includes an economic feasibility assessment. Study limitations include the absence of detailed uncertainty analysis and the assumption of constant hot-water demand. Future work should address measurement accuracy, dynamic load variations, and long-term system performance.